TRICHOBIZOAR - zeb, Aurang; Mohammad, Gul; Shah, S. Humayun (Journal of Ayub Medical College Abbottabad, 1991)
Persistent ingestion of non-nutritive substances such as dirt, clay, plaster, hair and paper is occasionally found in psychiatric practices (PICA). Ingestion of hair, trichopagia, is rarely encountered. Literature indicators as slight preponderance of black children with PICA compared with white children. Investigators have reported that PICA affects both sexes equally but in case of trichopagia there is a definite preponderance in females (4:1) One of the two theories about the etiology of PICA states that a specific nutritional deficit is present in the patients. The other theory postulates the unmet oral needs which are expressed in the persistent search for inedible substances. Poor supervision and neglect are often found childhood. Intestinal obstruction such as hair ball tumours, gastritis, hematemesis, perforation, zinc and iron deficiencies have been reported with trichopagia. We submit a report of two cases who are admitted as intestinal obstruction and hair ball tumours (trichbizoar) were found on laparotomy.